An Analysis of the profitability of commercial bank in China - xie, yuqing (2019)
The profitability of the Chinese banking industry is affected by many determinants. These factors include variables within each bank and several important macro variables that affect performance of commercial banks. The reasons for the impact of bank profitability may be related to government policies, we should take it seriously. Based on the annual data of 124 commercial banks in China in 2013-2018, we selected 9 variables include return on average assets (ROAA), capital adequacy ratio (EQTA), insolvency risk (Z-Score), bank size (TA), liquidity (NLTA), asset quality (LLRGL), cost efficiency (CTI), inflation rate (INF) and GDP growth rate (GDPGR). Using multi-collinearity, endogeneity test and GMM model to analyze the profitability of Chinese banking industry, it is concluded that the return on average assets of Chinese banking industry is positively correlated with GDP growth rate and insolvency risk and negatively correlated with bank size and cost efficiency. From the aspects of optimizing the Chinese banking business model, the government's policy towards on commercial banks and establishing a comprehensive financial supervision system to gives suggestions for increase the profitability of bank.